Wo die grünen Ameisen träumen - Marika, Wandjuk (Kinowelt Home Entertainment, 2005)
Lance Hackett is a sympathetic geologist working in Australia for an uranium mining company who must confront the passive resistance of the aborigine tribes. For the aboriginal people, the place where the deposits lay is considered the place "where the green ants dream" and for them this place is considered the origin of all life. In the clash with white imperialism, we see the irrevocable tragedy of false progress, in which civilization has lost touch with nature and the universe.
Bildformat: 1.85:1 (anamorph)
Orig.: Bundesrepublik Deutschland, Australien 1984
Enth. Audiokommentar von Werner Herzog und Laurens Straub. - Dokumentarfilm: "Wodaabe - Hirten der Sonne" (ca. 49 Min.). - Biografie Werner Herzog (Texttafeln). - Fotogalerie
Keywords: Aborigines; Aboriginal Australians -- Drama; Bororo (African people); Geologists -- Australia -- Drama; Herders -- Sahara; Sacred space -- Australia -- Drama; Uranium mines and mining -- Australia -- Drama; Australien